Product liability in comparative perspective / edited by Duncan Fairgrieve. - Fairgrieve, Duncan (Cambridge University Press, 2005)
This book examines the law of product liability from a comparative perspective. With the European Directive on Product Liability enacted over 20 years ago, this publication analyses the state of product liability in a number of key jurisdictions including both Western European countries and New Member States. Account is also taken of developments further afield, including the United States and Japan. Distinguished contributors, including a high court judge, European Commission official, leading litigators and academics, provide individual country reports and a number of integrated comparative studies. The book is designed for practical use by legal practitioners, academics, students and others interested in the area of contract, tort, civil procedure and multi-party litigation. In particular, practitioners will find the country reports an essential reference point.